THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. TIRTA INVESTAMA PANDAAN ON THE INCOME OF JATIANOM COMMUNITY - Harum Ayu Siswanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aimed to identifying the role of CSR (Corporate Social Responsibility) in promoting sustaitainable economy, this present study investigates the effect of CSR conducted by PT.Tirta Investama Pandaan on the income of the local community. The community development program of PT. Tirta Investama named Wanjati is conducted in Jatianom, Karangjati village and run under the mangement of Social Investment Indonesia (SII). By employing quantitative research method, this study randomly selects 78 respondents. The variables used in this study are training as dummy variable (D1), gender as dummy variable (D2), business as dummy variable (D3), capital (X1), age (X2), and income (Y). Jatianom as the sample since they are the beneficiaries of the CSR program.The data obtained in this study were analyzed by using multiple regression analysis with F test and T test. The findings show that training, capital, age, gender and capital and business simultaneously have significant effect on income. It shows that training and capital provision can increase the income of the community. The partial analysis reveals that training has significant effect on the increase of the community’s income. People who joined training have higher income compared to those who did not join the training. In addition, capital also has a significant effect on income which is greater (more dominant) than training, age, gender and business. It means the amount of the community’s income depends on how much the capital received. So, the higher the capital which is received, the higher the income of the community. Key point : CSR, , training, capital, income, community.